Effect of Population Lockdown on Pediatric Emergency Room Demands in the Era of COVID-19 - Valitutti, Francesco; Zenzeri, Letizia; Mauro, Angela; Pacifico, Rosario; Borrelli, Micaela; Muzzica, Stefania; Boccia, Giovanni; Tipo, Vincenzo; Vajro, Pietro (Frontiers in Pediatrics, 2020)
Objectives: The aim of this study was to assess the impact of COVID-19 pandemic and population lockdown on pediatric ED consultations. Methods: A cross-sectional study on pediatric emergency department consultations before and during the current COVID-19 pandemic (March -May 2019 vs March - May 2020) was performed in two hospitals in Campania region (Southern Italy), i.e. Salerno University Hospital (Salerno) and Pediatric Regional Referral Emergency Hub “AORN Santobono-Pausillipon” (Naples). Results: 29,368 consecutive ED pediatric patients (13,430 females; mean age ± SD= 5.4 + 4.7)years) were seen in March - May 2019 and 9,133 (4,494 females; mean age ± SD= 5.9 + 4.2 years) in March - May 2020. Resuscitation/emergency and urgent care pediatric ED consultations were 1,388 (4.7%, 95%CI 4.5-4.9) in 2019 trimester, while they were 648 (7.1%, 95% CI 6.6-7.6) in 2020 trimester (p<0.01). Mean pediatric ED daily consultations were 326.3 (95% CI 352.7-299.9) in the considered period of 2019 and 101.4 (95%CI 77.9-124.9) in the same period of 2020 (p<0.001). Covid-19 nasal swabs were performed for 385 children, of those 6 resulted positive and 4 of them were hospitalized. Conclusions: This work provides a unique snapshot of the pediatric EDs demands in the era of COVID-19. We witnessed a significant reduction of non-urgent health care demands during the pandemic but an increase of more severe urgent cases. COVID-19 pandemic and following lockdown unveiled the inappropriateness of the majority of pediatric ED consultations. Nevertheless, current scenario highlighted the need for appropriate and timely clinical evaluations in the pediatric primary care to tackle late and more severe diagnoses in EDs.